Implementasi Pelajaran Adab Islam di Ma’had Utsman bin Affan bin Baz 25 Jambi sebagai Landasan Etika dalam Era Society 5.0 - Sari, Fiqi Nurmanda; Irawan, Dedy; Sulistyo, Agus (YASIN, 2025)
Implementation of the Islamic Ethics curriculum at Ma’had and its impact on the behavior and character of the students in using technology. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving 3 students and 1 teacher. The results show that the Islamic Ethics lesson, which teaches noble moral values based on the Qur'an and Sunnah, is implemented using methods such as lectures, discussions, role-playing, and direct practice. The use of technology in the learning process also supports the effectiveness of teaching. The students demonstrate more polite, patient, and tolerant attitudes in social interactions, both in the real and digital worlds. However, challenges remain in teaching students to use technology wisely without neglecting Islamic values. Some suggestions from the students to improve the effectiveness of the learning process include adding practical activities, question-and-answer sessions, and mentoring programs. Overall, the Islamic Ethics lesson plays an important role in shaping students' character to be ethical and responsible in facing the challenges of the digital era.